Product development: e-personal possessions takaful (e-PPT) / Siti Hasnulbariah Ahmad Rusmili ... [et al.] - Ahmad Rusmili, Siti Hasnulbariah; Dal Nial, Nor Ashikin; Said, Dania Carmila; Mohammad Hatta, Mohammad Firdaus; Mat Nor, Norzanah (2021)
Nowadays, people are more exposed to crimes since the possibility for the act of crimes to befall onto them is anywhere regardless it is violent crimes or property crimes. In 2019, 16,489 violent crimes cases and 66,967 property crimes were reported. Thus, it is very important for people to protect themselves and their belongings. People nowadays own more valuable personal items as some of them have become necessities in life. A study is conducted to identify the solution for the damages or losses of personal possessions, hence new takaful product called e-Personal Possessions Takaful (e-PPT) that benefits contributors in terms of coverage for personal belongings, personal liability, and loss of use is introduced. Secondly, the study is keen to develop takaful coverage for personal possessions against certain risks for the e-PPT. Therefore, the closest products practices are used as a guideline. Simple mathematical calculation and Wakalah Integration Model for tabarru' fund is used to ensure the contribution amount collected per month is sufficient and the data is collected from websites articles. Lastly, the use of digitalization for e-PPT is examined by planning the outline for technology practices that can be applied to the takaful product. The result shows that e-PPT has the capability to provide protection to personal belongings at an affordable price. Plus, it can also provide wise coverages to the contributors and it is also an easy-access product due to the technology attached to it. So, it is hoped that with this product in the takaful market, people can be at ease knowing that their personal possessions are also able to be protected. It is also hoped that this takaful product can be an eye-opener for the takaful industry to produce more products that also target the youngsters.